RETRACTED ARTICLE: Silencing circular RNA-ZNF652 represses proliferation and EMT process of renal carcinoma cells via raising miR-205 - Ludong Zhang; Ya Guo (Artificial Cells, Nanomedicine, and Biotechnology)
We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article:Ludong Zhang & Ya Guo (2020) Silencing circular RNA-ZNF652 represses proliferation and EMT process of renal carcinoma cells via raising miR-205. Artificial Cells, Nanomedicine, and Biotechnology, 48(1), 648–655, DOI: 10.1080/21691401.2020.1725532Since publication it came to our attention that further information was required regarding the data presented and the methodological process of the reported research. We contacted the authors requesting their original data and details of the research protocol. In response, the authors have requested retraction of their article because they acknowledge their research did not comply with the journal's research ethics policies on human research. In addition, they were unable to provide their original data to the journal to verify its authenticity. The authors, Editor and Publisher all agree retraction of the article is necessary to ensure the integrity of the scholarly record.We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.